مسرحية ساره كين (التطهير) انموذجا للأضطهاد في العصر الحديث (مجلة جامعة بابل للعلوم الانسانية, 2019)
Sarah Kane is one of the important playwrights in the modern theatre.She has been criticized severely due to the scenes in her plays. Cleansed is distinguished by the shocking actions done by the characters. The senses of oppression and violence are dominating the behavior of characters leading to scenes that are against the human nature.